Inspiring Future: Motivational Program for Visually Impaired Students toward Higher Education in Information Technology at Malaysian Association for the Blind (MAB) - Ahmad Musyafa; Lisda Fitriana Masitoh; Joko Riyano; Nani Rusnaeni; Teti Desyani; Okta Irawati; Zurnan Alfian (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
Inclusive education is a crucial effort to ensure equitable access to education for all, including those with visual impairments. Although technological advances have made learning easier for visually impaired students, challenges remain that affect their motivation to pursue higher education. Limited information, low self-confidence, and stigma regarding the academic abilities of people with visually impaired are some of the frequently encountered barriers. This international community service program aims to increase the motivation, self-confidence, and insight of visually impaired students regarding higher education opportunities, particularly in the fields of information technology and computer engineering. The program was held on May 18, 2026, at the Malaysian Association for the Blind (MAB) in Kuala Lumpur, Malaysia, and involved 12 visually impaired students. The program included the delivery of motivational materials, an introduction to inclusive higher education, reinforcement of simple logic and mathematics, and interactive discussions. The program demonstrated high levels of enthusiasm among participants. Participants gained new insights into opportunities for continuing higher education, support for inclusive campuses, and the use of assistive technology in the learning process. This activity positively impacted participants' motivation and confidence to pursue higher education. Furthermore, it strengthened the role of higher education institutions in supporting inclusive education and equitable access to education for visually impaired students.